BUSINESS STRATEGY AND FINANCIAL PERFORMANCE AS MEDIATION VARIABLES IN THE RELATIONSHIP OF CORPORATE GOVERNANCE TO EARNING QUALITY OF PUBLIC COMPANIES IN ASEAN - Molina; Mediaty; Asri Usman; Bambang Subiyanto; Median Wilestari (SEAN Institute, 2022)
This study aimed to analyze the effect of corporate governance mechanisms on earnings quality with business strategy and financial performance as mediating variables. The analysis was carried out using the SEM-Warp PLS 7.0 application with two relationship models; direct and mediation. The first test analyzes the direct effect of corporate governance mechanisms on earnings quality. The corporate governance mechanism is measured by four proxies (number of commissioners, percentage of independent commissioners, percentage of audit committees with financial or accounting education background, and percentage of public ownership); and earnings quality as measured by four proxies (persistence, predictability, variability, and smoothness). The mediating effect of business strategy and financial performance is measured by proxy of intangible asset value and ROA analyzed through the indirect model. The results obtained in this study are different from result of previous studies that show corporate governance mechanisms in public companies in ASEAN have a negative effect on earnings quality. However, business strategy and financial performance partially mediate (competitive mediation) to function as a suppressive or substitute effect. This explain why the overall effect of corporate governance mechanisms on public companies in the ASEAN region has been significantly practised in many previous studies.